Position Angle Distribution of Galaxies in 35 Cluster - Yadav, Shiv Narayan; Aryal, Binil; Saurer, Walter (Himalayan Physics, 2013)
We worked on POSSII and ESO films and measured the diameters and position angles of 5 688 galaxies in 34 clusters using 25-fold magnification microscope. The position angle distributions of galaxies in the clusters are studied. For this, chi-square, auto-correlation and the Fourier tests are carried out. The preferred position angle distribution of galaxies in the cluster is found to be independent of the mean radial velocity of the cluster. Possible explanations of the result will be discussed. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 1-9 Uploaded date: 12/22/2013